Unfavorable Outcome of Neuroblastoma in Patients With 2p Gain - Szewczyk, Katarzyna; Wieczorek, Aleksandra; Młynarski, Wojciech; Janczar, Szymon; Woszczyk, Mariola; Gamrot, Zuzanna; Chaber, Radosław; Wysocki, Mariusz; Pogorzała, Monika; Bik-Multanowski, Mirosław; Balwierz, Walentyna (Frontiers in Oncology, 2019)
BACKGROUND: The amplification of MYCN oncogene is the most unfavorable genetic factor in neuroblastoma patients. However, the knowledge about the clinical impact of low-level multiplication of MYCN is still insufficient. Therefore, we aimed to investigate the disease course in patients with different copy number status of MYCN. MATERIAL AND METHODS: We examined 105 children diagnosed with neuroblastoma from 2010 to 2018 in five pediatric oncology centers in Poland. We determined the MYCN status at diagnosis by the interphase FISH examination and assessed the clinical outcome in patients. RESULTS: A total of 35% of tumors presented with chromosome 2 numerical changes, 20% had MYCN amplification and 16% revealed 2p gain. Unexpectedly, we observed very low overall survival and event free survival rates in neuroblastomas with 2p gain, which were comparable with patients with MYCN amplification. CONCLUSIONS: The 2p gain alteration should be reported as strong unfavorable prognostic marker in neuroblastoma patients.